Prognostic role of tumour-infiltrating lymphocytes assessed by H&E-stained section in gastric cancer: a systematic review and meta-analysis. Issue 1 (31st January 2021) - Tian, Chunfang; Jing, Haiyan; Wang, Caixia; Wang, Weibo; Cui, Yangang; Chen, Jianpeng; Sha, Dan
Abstract : Objectives: Some studies have identified tumour-infiltrating lymphocytes (TILs) in H&E-stained sections of gastric cancer, but the prognostic and clinicopathological significance of this remains unclear. The objective of this study is to evaluate the associations between H&E-based TIL density and prognosis and clinicopathological characteristics of patients with gastric cancer. Design: Systematic review and meta-analysis. Data sources: Cochrane Library, PubMed and Embase databases were searched through 25 February 2020. Eligibility criteria: Studies evaluating the correlations between TILs assessed by H&E-stained sections and prognosis and clinicopathological characteristics of gastric cancer were included. Data extraction and synthesis: Relevant data were extracted and risks of bias were assessed independently by two reviewers. HR and relative risk (RR) with 95% CI were pooled by random-effect models to estimate the associations between TIL density and overall survival (OS) and clinicopathological characteristics, respectively. Results: We enrolled nine studies including 2835 cases for the present meta-analysis. High TILs were associated with superior OS (HR=0.68, 95% CI 0.52 to 0.87, p=0.003) compared with low TILs. High TILs were significantly associated with lower depth of invasion (T3–T4 vs T1–T2) (RR=0.58, 95% CI 0.50 to 0.66, p<0.001), less lymph node involvement (presence vs absence) (RR=0.68, 95% CI 0.56 to 0.81, p<0.001) and earlier TNM (tumour, node, metastasis) stage (III–IV vs I–II) (RR=0.68, 95% CI 0.55 to 0.83, p<0.001). TIL density was not associated with age, gender, Lauren classification or histological grade. The methodology for evaluating TIL and its cut-off value varied across different studies, which might affect the results of our meta-analysis. Conclusions: Our meta-analysis suggests that H&E-based TIL density is a reliable biomarker to predict the clinical outcomes of patients with gastric cancer. Multicentre, prospective studies are needed to further confirm our findings. PROSPERO registration number: CRD42020169877.